한국 물리치료 학술지에 무작위대조연구의 비뚤림 위험 평가: 2018~2022년 검토 - 임재현; 박치복; 김병근; Jae Hyun Lim; Chi Bok Park; Byeong Geun Kim (대한물리치료과학회지, 2023)
Background: Randomized controlled trials (RCTs) provide evidence on the effectiveness and safety of interventions and inform systematic reviews and guideline preparation for clinical application. However, methodological flaws can occur in many RCTs, and Cochrane's risk of bias version 2 (RoB2) can be used to evaluate RCTs' risk of bias (RoB). However, physical therapy RCTs in Korea did not confirm RoB. Therefore, the purpose of this study was to evaluate RoB using RoB2 in RCTs published in the Korean Physical Therapy Journal. Design: Review. Methods: The RCTs subject to evaluation were RCTs published in 11 physical therapy journals in Korea from 2018 to 2022. RoB2 evaluated a total of five domains: bias arising from the randomization process, bias due to deviations from intended interventions, bias due to missing outcome data, bias in measurement of the outcome, and bias in selection of the reported result. Results: A total of 616 RCTs were evaluated. As for bias arising from the randomization process, high risk was the highest at 555 (90.1%), followed by low risk at 41 (6.7%) and some concerns at 20 (3.2%). For bias due to deviations from intended interventions, the proportion of some concerns was the highest at 390 (63.3%), followed by high risk at 218 (35.4%) and low risk at 8 (1.3%). As for the bias due to missing outcome data, the rate of low risk was the highest at 399 (64.8%), followed by high risk at 159 (25.8%) and some concerns at 58 (9.4%). As for bias in measurement of the outcome, high risk was the highest at 294 (47.7%), followed by low risk at 224 (36.4%) and some concerns at 98 (15.9%). In the bias due to missing outcome data, the ratio of high risk was the highest at 610 (99%), followed by low risk at 4 (0.7%) and some concerns at 2 (0.3%). Conclusion: Most of the RoB evaluation results of RCTs published in the Korean Physical Therapy Journal were rated as high risk. Methodological quality of RCTs needs to be improved.